Crystal Structure and Improved Synthesis of 1‐(2H‐Tetrazol‐5‐yl)guanidium Nitrate. Issue 4 (25th April 2016) - Nimesh, Sasidharan; Ang, How‐Ghee
Abstract: Energetic derivatives of tetrazoles are one of the key areas of research focus in pursuit of novel high energy materials, useful as propellants and explosives. Herein, the crystal structure and an improved synthetic procedure of 1‐(2H‐tetrazol‐5‐yl)guanidine (1 ) and its nitrate salt (2 ) are reported. The compounds were structurally characterized by spectroscopic (FT‐IR, 1 H NMR, 13 C NMR) and elemental analysis. The molecular structure of tetrazolyl guanidium nitrate (2 ) was solved using low temperature single‐crystal X‐ray diffraction.2 crystallized as its hemihydrate in the orthorhombic space group Fdd 2, with a crystal density of 1.69 g cm −3 . Thermal behavior and decomposition of the molecules were studied with differential scanning calorimetry (DSC). Molar enthalpy of formation (Δf H m ) of compound2 was back calculated from heat of combustion (Δc H 0 ) value obtained experimentally using bomb calorimetric measurements. Lattice enthalpy of 1‐(2H‐tetrazol‐5‐yl)guanidium nitrate was directly calculated from measured crystal density using Jenkins equation. Preliminary ballistic parameters of the compound were predicted and compared with reported high nitrogen tetrazole derivatives. Abstract :